Adaptation of O157:H7 and non-O157 Escherichia coli strains in orange juice and subsequent resistance to UV-C radiation - Oteiza, Juan Martín (2022)
This study assessed the acid-adaptation of pathogenic and non-pathogenic strains of Escherichia coli in orange juice and the microbial resistance to the subsequent UV-C radiation treatment. Nine Shiga toxin-producing E. coli (STEC) and one strain of a non-pathogenic surrogate E. coli were used in this study. Each E. coli strain was inoculated in orange juice, following pre-exposure during 0, 1, 2, and 3 h at 10 °C. Then, the inoculated juices with the ten different strains separately were exposed to 0 and 2 J/cm2 of UV-C radiation. The D value (i.e., the UV-C dose in J/cm2 required to cause a one-log reduction in the target microorganism) was calculated. Further, the resistance coefficient [RC; i.e., the ratio between the D-values for the control condition (D0h) and each pre-exposure tested time (D1h, D2h, D3h)] were determined. The results indicated that the resistance of E. coli was influenced by the pre-exposure period in the orange juice, with increased resistance to UV-C observed for periods >2 h. Furthermore, the sensitivity of cells to subsequent UV-C treatment was found to be strain-dependent. The results may allow the development of more reliable UV-C radiation processes for orange juice processing aiming the inactivation of pathogenic E. coli.